2020
DOI: 10.2174/1874350102013010123
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Emotional Support Scale on Italian High School Students: A Contribution to the Validation

Abstract: Background/Objective: This study represents a contribution to the validity and reliability of the 15-item Teacher Emotional Support Scale in a sample of Italian high school students (N=501; 80.2% females; M=15.66; SD=1.52). Therefore, the present paper aimed to examine the factor structure and to investigate the reliability and validity of the scale. Students’ perception of teacher emotional support refers to the students’ perception of whether and to what extent the teacher shows caring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Previous scholars, indeed, have highlighted that students’ perception of teachers’ emotional support was inversely related to emotional problems and adverse school outcomes (e.g., [ 97 ]). Moreover, students who perceive their teacher as caring and attentive to their emotional needs may feel more shielded and have further possibilities to counteract the strain and pressure of excessive school requirements (e.g., [ 47 , 98 , 99 , 100 ]). Besides this, considering that emotional consumption is the first and foremost component experienced by burned-out students [ 101 ], the ones who perceived high emotional and caring behavior from their teachers are more likely to broaden their emotional resources and overcome the burnout-related exhaustion (e.g., [ 3 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous scholars, indeed, have highlighted that students’ perception of teachers’ emotional support was inversely related to emotional problems and adverse school outcomes (e.g., [ 97 ]). Moreover, students who perceive their teacher as caring and attentive to their emotional needs may feel more shielded and have further possibilities to counteract the strain and pressure of excessive school requirements (e.g., [ 47 , 98 , 99 , 100 ]). Besides this, considering that emotional consumption is the first and foremost component experienced by burned-out students [ 101 ], the ones who perceived high emotional and caring behavior from their teachers are more likely to broaden their emotional resources and overcome the burnout-related exhaustion (e.g., [ 3 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, teacher sensitivity concerns the extent to which a teacher is prone to respond to students' academic and emotional needs. Finally, a regard for adolescent perspective pertains to the degree to which teachers promote the autonomy and general development of their students [46][47][48][49]. Previous studies have shown that, compared to other sources of support, high school students' perception of teacher emotional support is more strongly associated with low levels of emotional exhaustion and high subjective well-being (e.g., [50,51]).…”
Section: School Burnout and Students Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, two previous studies addressed this issue, showing that perceived teacher emotional support and its dimensions were significantly and negatively related to high school students’ burnout. However, both studies used the cross-sectional approach [ 19 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This variable is related with a lesser frequency of student misbehaviour in the classroom [ 11 , 26 , 30 ]. The cultivation of a good relationship with students is associated with the teacher profile characterised by using rewards, dialogue, teacher sensitivity, and regard for adolescent perspective, acknowledging own responsibility, and so on [ 33 , 40 , 41 ]. In general terms, encouraging participation in classrooms by respecting one another and promoting coexistence are good practices that encourage excellent student–teacher relationships and ensure greater teacher competence [ 33 ].…”
Section: Introductionmentioning
confidence: 99%